Identification of risk factors for recurrent febrile convulsion - Nadirah Rasyid Ridha; P. Nara; Hadia Angriani; Dasril Daud (Indonesian Pediatric Society Publishing House, 2009)
Background Febrile convulsion (FC) occurs in about 2 to 4 percent of all children, approximately one third of whom will then develop recurrent febrile convulsion (RFC). Risk factors for RFC are family history of convulsions, an age of less than 18 months, a relatively lower temperature and shorter duration of fever preceeding the first FC. Objective The aim of the study was to determine the risk factors for RFC. Methods One hundred children aged 6 months to 5 years with FC or RFC were included in this case-controlled study, which was carried out from July 2006 to June 2007. Data on the children's first FC were collected from medical records and the family history was taken directly from the parents. Results Fifty children with RFC and 50 children without recurrence were included in this study. An age of less than 18 months (P< 0.0001, COR= 71.37), a family history of FC (P< 0.0001, COR= 6.00), and a fever duration ofless than 12 hours preceding the first FC (P< 0.0001, COR = 4.96) were associated with a risk of recurrence. A relatively lower degree of temperature at first febrile convulsion did not increase the risk for RFC (P = 1.21). Multivariate logistic regression showed that younger age and shorter duration of fever preceding the first FC were associated with RFC. Conclusion Younger age and shorter duration of fever preceding the first FC are associated with an increased risk ofRFC.